Hubungan Pengetahuan Tentang Tanda Bahaya Dalam Kehamilan Dengan Keteraturan Antenatal Care Di Puskesmas Batua Kecamatan Manggala Kota Makassar - Kasmawati Kasmawati; Jumrana Jumrana (The Journal General Health and Pharmaceutical Sciences Research, 2023)
The aim of this research is to determine the relationship between knowledge about danger signs in pregnancy and the regularity of Antenatal Care at the Batua Community Health Center, Manggala District. The research design used in this study is observational with a "Cross Sectional Study" approach, where the dependent variable and independent variables are collected simultaneously at the same time to obtain information about the relationship between pregnant women's knowledge about danger signs in pregnancy and the regularity of Antenatal Care. The population in this study were all 45 mothers who had their pregnancy checked. The sampling technique in this research was purposive sampling so that the sample obtained was 35 people. Data collection was obtained through questionnaires given directly to respondents. The data analysis techniques used are bivariate analysis and univariate analysis. The research results showed that knowledge of pregnant women about danger signs in pregnancy was mostly in the good category, namely 25 people (80.6%), the regularity of Antenatal Care among pregnant women was mostly in the regular category, namely 21 people (67.7%), and knowledge about danger signs in pregnancy. with the regularity of Antenatal Care for pregnant women at the Batua Community Health Center, Manggala District, Makassar City for the period February 2022 (p=0.003).